Efektivitas Pendekatan Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematis - Cici Herlina; Casnan Casnan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The problem in this study is the low mathematical problem solving of students. This study aims to determine the effectiveness of the Realistic Mathematics Education (RME) approach to mathematical problem solving abilities. The method in research is quantitative method. The type of research used to investigate causal relationships is quasi-experiment where experimental units are divided into experimental groups and control groups without randomization. The research design chosen is Non-equivalent control group design. This research will be carried out at SMP Negeri 1 Ciautumn in February 2023. Samples were taken by purposive sampling consisting of classes VII A and B (Experimental Class) and classes VII C and D (Control Class). The number of students of both classes is the same which is 24 students, a total sample of 48 students. The results of the hypothesis test on the results of post-test data showed that there was a significant difference between students' mathematical problem solving abilities after applying the Realistic Mathematics Education (RME) approach in the experimental class and the conventional model of the control class. There was a significant improvement in students' mathematical problem-solving ability in the experimental group compared to students' mathematical problem-solving skills in the control group